1979
DOI: 10.1073/pnas.76.10.4867
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary structure of the ribosomal 30S subunit: model and its experimental testing.

Abstract: In considering the structure of the 30S subunit of the Escherichia coli ribosome, we have assumed that: (l) all or almost all the proteins within the 30S particle are compact and globular, as recently shown for the isolated proteins S4, S7, S8, S15, and S16 in solution [Serdyuk, I. N., Zaccai, G. & Spirin, A. S. (1978) In recent years, the technique of chemical crosslinking of neighboring proteins by bifunctional reagents and measurements of the distances between deuterated or fluorescent-labeled proteins by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1980
1980
1999
1999

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…This argument does not seem to hold, since the R g TP30 evaluated from the triangulation map without S1 is 6.34 nm and thus not signi®-cantly different from that of the entire moiety. Our model displays a much better agreement with the model of the 30 S subunit proposed by Spirin et al (1979), which combined the protein positions with the V-shaped rRNA model by Vasiliev et al (1978). As seen from Figure 9(b), most of the proteins in the map by Spirin et al (1979) are positioned inside the gap between the envelope of the entire subunit and that of the rRNA moiety, whereas the lines representing the main axes of the V-shaped 16 S Solution Scattering Analysis of 70 S Ribosome.…”
Section: Comparison Of the Optimized Four-phase Model With Models Frosupporting
confidence: 76%
“…This argument does not seem to hold, since the R g TP30 evaluated from the triangulation map without S1 is 6.34 nm and thus not signi®-cantly different from that of the entire moiety. Our model displays a much better agreement with the model of the 30 S subunit proposed by Spirin et al (1979), which combined the protein positions with the V-shaped rRNA model by Vasiliev et al (1978). As seen from Figure 9(b), most of the proteins in the map by Spirin et al (1979) are positioned inside the gap between the envelope of the entire subunit and that of the rRNA moiety, whereas the lines representing the main axes of the V-shaped 16 S Solution Scattering Analysis of 70 S Ribosome.…”
Section: Comparison Of the Optimized Four-phase Model With Models Frosupporting
confidence: 76%
“…The protein $9/S11 was shown earlier to be crosslinked with tRNA Phe in the ribosomal P-site after UV-irradiation (X = 254 nm) [14]. Using the method of reconstruction of ribosomal subunits from the proteins and rRNA after chemical modification of proteins it was shown that proteins S11 and $21 directly participate in tRNA-binding centre formation [20]. The proteins modified by photoreactive tRNA Phe analog in the ribosomal P-site according to our data are shaded.…”
Section: Resultsmentioning
confidence: 99%
“…Participation of the 50 S proteins L11, L13, L14 and L27 in P-site formation was shown using different tRNA derivatives containing reactive groups in the aminoacyl residue [17,18]. To date, several models are known of 30 S ribosomal subunit from E. coli obtained by different methods [19][20][21][22] for describing positions of proteins on the surface of the 30 S subunit. On the model in [21] which is the most complete for antigen determinants of the ribosomal proteins one can incorporate proteins found in the P-site according to our data into a compact group (see fig.4a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to three-dimensional model of the 30S subunit, this protein is localized in the head region (2,3,24). Moreover, S13 has been shown to assemble directly with the 3Ј domain of the 16S RNA in stoichiometric amounts (6).…”
Section: Discussionmentioning
confidence: 99%